Effects of cytokinin and paclobutrazol application time on growth and yield of G2 potato (Solanum tuberosum L.) Medians cultivar at medium altitude in Indonesia - Anne Nuraini; Nugroho, Paramita Salsabila; Sutari, Wawan; Syariful Mubarok; Jajang Sauman Hamdani (Agriculture and Natural Resources, 2021)
Many efforts have been made to optimize the growth of potato plants at medium altitude, including the addition of the growth regulators cytokinin and paclobutrazol, which regulate the balance of sources and sinks. This study examined the effect of the application times of cytokinin and paclobutrazol on the growth and yield of G2 potato at low and medium altitude. An experiment was carried out in the Ciparanje Experimental Garden, Jatinangor, at 685 m above sea level in Inceptisol soil. The experiment used a randomized complete block design with the following treatments: no cytokinin or paclobutrazol (control), only cytokinin applied at 30 d after planting (DAP), paclobutrazol applied at 30 DAP, combinations of cytokinin applied at 20 DAP, 30 DAP and 40 DAP and paclobutrazol applied at 40 DAP, 50 DAP and 60 DAP. The concentrations were 100 ppm for both cytokinin and paclobutrazol. The results showed that the application of cytokinin at 30 DAP and paclobutrazol at 40 DAP produced the highest numbers of G2 seed tubers (Class S/<40 g: 84.36 ± 8.93) but resulted in a statistically comparable tuber weight per plant (349.25 ± 68.65 g) compared with the control (283.33 ± 31.47 g). High tuber weights per plant were obtained with the application of only cytokinin at 30 DAP (450.28 ± 13.90 g), the combination of cytokinin at 20 DAP + paclobutrazol at 40 DAP (483.33 ± 47.14 g) and the combination of cytokinin at 30 DAP + paclobutrazol at 50 DAP (478.72 ± 42.76 g).